POLA ASUH KELUARGA PETANI DI DESA LOKLAHUNG KECAMATAN LOKSADO KABUPATEN HULU SUNGAI SELATAN - Nadia Nadia (JURNAL SOCIUS, 2015)
This study aimed to describe parenting peasant family in the Loklahung village. The method used is qualitative descriptive method. The results showed family upbringing farmers in the Loklahung in education patterns parenting authoritative (democratic), in terms of discipline pattern of parenting authoritarian, the impact of social changes that occur in the family in the Loklahung village not only the mother who is in charge of taking care of children but father also took part in parenting and the mother is also involved in making a living as farm stays and weaving baskets, and parenting peasant family in the village of Loklahung in shaping children's character based on the character values such as the nature respect and respect for others are responsible, fair, and caring social studies can be used as a source of learning that focuses on value (value-based).Keywords: parenting, family farmers, values, social studies learning